Caracterização molecular do gene que codifica a TCTP (Translationally Controlled Tumor Protein) em tomate (Solanum lycopersicum cv. Santa Clara) - Araujo, Laura Migliorini de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The gene encoding TCTP (Translationally Controlled Tumour Protein) is present in all eukaryotes and its product is involved in various cellular processes. Although well characterized in mammals, there are only few works available in the literature related to the analysis of this protein in plants. In this present work, the expression of the gene encoding TCTP was analyzed in different organs/tissues of tomato plants (Solanum lycopersicum cv. Santa Clara). A quantification performed by RT-qPCR revealed the presence of TCTP transcript in all tissues/organs analyzed, with the highest expression level found in leaves. With the exception of fruits in intermediate stage of maturation, for which a small increase on the expression was detected, there was minimal variation in the relative expression of TCTP in other organ/tissues. In parallel, the effects of the constitutive expression of TCTP were investigated using transgenic tobacco lines able to overexpress this protein at different levels (T1, T2 and T3). Seedlings of these lines, and of a non-transgenic control line, were grown in MS culture medium for 21 days. At the end of this period, the length of roots and leaves was taken and the seedlings were photographed. According to Tukey's test, the analysis of the mean root length revealed a significant difference between T1 and T3 lines when compared to the control, although the same was not observed for the T2 line. For leaves, according to Kruskal-Wallis test, there was a statistical difference between the averages of leaf growth obtained for the different lines evaluated. According to these results, we can conclude that TCTP shows an ubiquitous expression in tomato plants, with the highest expression detected in leaves, and also that its overexpression promoted a higher root and leaf development in two of three transgenic tobacco lines tested

O gene que codifica a TCTP (Translationally Controlled Tumour Protein) está presente em todos os eucariontes e o seu produto está envolvido em diferentes processos celulares. Embora bem caracterizada em mamíferos, poucos são os trabalhos disponíveis na literatura relacionados à análise dessa proteína em plantas. No presente trabalho, a expressão do gene que codifica a TCTP foi analisada em diferentes órgãos/tecidos do tomateiro (Solanum lycopersicum cv. Santa Clara). A quantificação, realizada por RT-qPCR, revelou a presença do transcrito da TCTP em todos os diferentes tecidos/órgãos analisados, sendo o maior nível de expressão encontrado nas folhas. Com exceção de frutos em estágio intermediário de maturação, em que foi detectado um pequeno aumento, a variação na expressão relativa da TCTP para os demais órgãos/tecidos foi mínima. Paralelamente, os efeitos da expressão constitutiva da TCTP foram investigados empregando linhagens transgênicas de tabaco capazes de superexpressar essa proteína em diferentes níveis (T1, T2 e T3). Plântulas das referidas linhagens, e de um controle não transgênico, foram cultivadas em meio de cultura MS durante 21 dias. Ao final desse período, o comprimento das raízes e das folhas foi registrado e as plântulas fotografadas. Através do Teste de Tukey, a análise das médias do comprimento da raiz revelou uma diferença significativa entre as linhagens T1 e T3 em relação ao controle, ao passo que o mesmo não foi verificado para a linhagem T2. Para as folhas, segundo o teste de Kruskal-Wallis, diferenças estatísticas entre as médias de crescimento em cada uma das linhagens avaliadas foram detectadas. Pelos resultados obtidos, pôde-se constatar o caráter ubíquo da TCTP em tomate, sendo sua maior expressão detectada em folhas, e, ainda, que sua superexpressão promoveu um maior crescimento radicular e foliar em duas das três linhagens transgênicas de tabaco testadas
Keywords: Genetica molecular; Tomate - Pesquisa; Genetica vegetal